The I-opener : an introduction to philosophy - Platt, Robert M. (Englewood Cliffs, N.J. : Prentice Hall, 1976)
An introduction to philosophy using contemporary examples to illustrate classical philosophical problems.
Bibliography: p. 263-265.
Keywords: Philosophy -- Introductions; Philosophy